A Literature Review on Drip Irrigation System - N. N. Saxena (International Journal of Modern Agriculture, 2021)
Land and water represent the country's fundamental needs for agriculture and economic growth. By 2025, 1/3 of the world's population will face total water shortage. Agriculture consumes over eighty percentage of the exploitable water supplies of the world. The global productivity of the agricultural sector & the expected rate of development in GDP entirely rely primarily on the sagacious utilize of the obtainable water supplies. Therefore, this Micro Irrigation scheme which aim to increase the region under the efficient irrigation techniques via irrigation by Drip technique. Drip irrigation is the effective way of delivering irrigation of water directly to soil in the plant's root areas, reducing typical mislaying such as soil erosion, deep percolation and runoff. This also permits fertilizers, nutrients, & other water-soluble substances to be used along with irrigation water, leading to higher yields and improved production results. Drip irrigation systems is seen the solution to several challenges of dry land cultivation and increasing the output of irrigated cultivation. In view of all these, the present research was planned to research the degree of advantages obtained from drip irrigation in horticultural crops and to recognize the constraints faced by farmers in the adoption of the drip irrigation in horticultural crops.